Raising chickens for dummies - Willis, Kimberley; Ludlow, Rob. (Hoboken, NJ : Wiley Pub., 2009)
Presents a guide to caring for chickens on a small scale, including purchasing a starter flock, housing, feeding, care, and raising the animal for specific purposes such as food.
Includes index.
Keywords: Chickens